HYBRID ALGORITMA BAT DAN HARMONY SEARCH UNTUK MENYELESAIKAN DYNAMIC TRAVELLING SALESMAN PROBLEM - Irvayanto Akbar Pamungkas (SCIENCE MATH: Jurnal Ilmu Sains dan Matematika, 2025)
This research aims to solve the Dynamic Travelling Salesman Problem (DTSP) using hybrid Bat algorithm and Harmony Search. Dynamic Travelling Salesman Problem (DTSP) which is a development of Travelling Salesman Problem (TSP) of which is a problem that aims to find the route with shortest distance in visiting several cities. In DTSP, the cities that should be visited can be changed any time. This changed can be the addition of cities or the deletion of cities that should be visited. Bat Algorithm (BA) is a an optimization method inspired by the echolocation behavior of bats act as a signal system to sense distance and location of prey. Harmony Search Algorithm (HSA) is an optimization method that is based on natural musical performance processes that occur when a musician searches for an optimal state of harmony. The hybrid Bat algorithm and Harmony Search can be applied to solve the Dynamic Traveling Salesman Problem (DTSP) with 9 steps, starting from parameter initialization to updating the cities.